A systematic review on technologies and industry 4.0 in the forest supply chain: A framework identifying challenges and opportunities - Zhaoyuan He; Paul Turner (Logistics, 2021)
Background: Forestry products and forestry organizations play an essential role in our lives and significantly contribute to the global economy. They are also being impacted by the rapid development of advanced technologies and Industry 4.0. More specifically, several technologies associated with Industry 4.0 have been identified for their potential to optimize traditional forest supply chains. However, to date, there has been limited research that has systematically investigated these technologies and the scientific evidence on their impact on forest supply chains. This research systematically reviews the state-of-the-art technologies applied in the forest supply chain and reports on the current (and/or potential) impacts of technologies on the transformation of the forest supply chain towards "Forest Industry 4.0". Methods: The systematic literature review methodology identified 45 peer-reviewed studies for inclusion that are analyzed, interpreted and discussed in this paper. Results: This study developed a framework on the forest supply chain in Industry 4.0. This framework has three components related to forest supply chains: current supportive technologies, improvements and characteristics of the forest supply chain in Industry 4.0, and the strategic outcomes in economic, environmental and social dimensions. The reported impacts of technologies in different phases of the forest supply chain are interpreted and discussed. Conclusion: The study results confirm that most technologies in Industry 4.0 have real or perceived positive impacts on the forest supply chain and reported obstacles and challenges are identified. The results of this study also contribute insights on the wide range of options in terms of technologies available to decision-makers to optimize the forest supply chain towards "Forest Industry 4.0".
Keywords: 650; forest products; forest supply chain; Industry 4.0; Industry 4.0 framework; systematic literature review